Analisa faktor yang mempengaruhi lansia dalam pemanfaatan posyandu lansia di Kelurahan Tangkerang Timur Kecamatan Tenayan Raya - Rosmeri Bukit (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
ABSTRACT Indonesia has entered the era of aging population. The percentage of the elderly population is expected to continue to increase. Based on data from the Directorate General of Population and Civil Registration (Dukcapil), the Indonesian population aged 60 years and over or the elderly (elderly) is 30.16 million people in 2021. In 2045, BPS predicts that 19.90% of Indonesia's total population will be elderly. The United Nations estimates that there will be 727 million people aged 65 years or older in 2020. This number will double to 1.5 billion in 2050. This trend of increasing elderly population needs special attention, especially for improving the quality of life of the elderly. This research was conducted to find out what factors influence the elderly in utilizing the elderly Posyandu. The research design used was a cross sectional study and the sampling and sampling technique used was random sampling, with a total sample of 100 people.Based on the results of the research and discussion, it can be concluded that the factors related to the utilization of the elderly posyandu by the elderly consist of factors of gender, age, education, knowledge, level of activity of cadres, access to affordability and services of the elderly posyandu. Meanwhile, work and family support for the elderly are not factors for the elderly in the use of posyandu for the elderly